2015
DOI: 10.1016/j.apsb.2015.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of direct inhibitors of Keap1–Nrf2 protein–protein interaction as potential therapeutic and preventive agents

Abstract: The Keap1–Nrf2–ARE pathway is an important antioxidant defense mechanism that protects cells from oxidative stress and the Keap1–Nrf2 protein–protein interaction (PPI) has become an important drug target to upregulate the expression of ARE-controlled cytoprotective oxidative stress response enzymes in the development of therapeutic and preventive agents for a number of diseases and conditions. However, most known Nrf2 activators/ARE inducers are indirect inhibitors of Keap1–Nrf2 PPI and they are electrophilic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
184
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 254 publications
(186 citation statements)
references
References 117 publications
(214 reference statements)
0
184
2
Order By: Relevance
“…Exposure to cigarette smoke causes more severe emphysema-like symptoms, and is associated with oxidative DNA adduct formation, apoptosis, and elevated Nrf2 expression (5,10). Nrf2 has an essential protective role in the lungs against oxidative airway diseases, by controlling the expression of antioxidant response element-regulated antioxidant and cytoprotective genes (7). However, the present study showed no significant correlation between smoking status and the expression level of Nrf2 in PSP patients ( Table 2).…”
Section: Discussioncontrasting
confidence: 51%
See 2 more Smart Citations
“…Exposure to cigarette smoke causes more severe emphysema-like symptoms, and is associated with oxidative DNA adduct formation, apoptosis, and elevated Nrf2 expression (5,10). Nrf2 has an essential protective role in the lungs against oxidative airway diseases, by controlling the expression of antioxidant response element-regulated antioxidant and cytoprotective genes (7). However, the present study showed no significant correlation between smoking status and the expression level of Nrf2 in PSP patients ( Table 2).…”
Section: Discussioncontrasting
confidence: 51%
“…Under normal conditions, Nrf2 is sequestered in the cytosol and bound to the actin cytoskeleton by Kelchassociated protein 1, a cytosolic regulatory protein. When oxidative stress occurs, Nrf2 translocates into the nucleus and binds to the promoter sequence of antioxidant genes (7). In some pulmonary diseases, Nrf2 plays a cytoprotective role by induction of a suite of various antioxidants and phase II enzymes to restore redox homeostasis (7).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The discovery of new peptides and small-molecule inhibitors of the KEAP1/NRF2 interaction has been reviewed recently (Abed et al, 2015;Jiang et al, 2016). Briefly, a series of truncated NRF2 peptides was initially evaluated as direct inhibitors of PPI using surface plasmon resonance and fluorescence polarization assays (Hu et al, 2013).…”
Section: B Protein-protein Interaction Inhibitors For Nuclear Factormentioning
confidence: 99%
“…The high electrophilicity of traditional Nrf2-activators poses the risk of ''off-target'' effects due to their ability to react with the cysteines of other proteins. Therefore, there has been an increased interest in the direct targeting of Nrf2/Keap1 protein-protein interaction (PPI) as an alternative strategy (recently reviewed by Wells 162 and Abed et al 163 ). High-throughput screening using fluorescence polarisation (FP) assay yielded several micromolar hits 164,165 .…”
Section: Synthetic Nrf2 Activatorsmentioning
confidence: 99%